Solution processed cellulose/melanin films and fibres - Farsa, Ram; Pimpalkar, Nikhil; Shete, Abhijit P.; Shanmuganathan, Kadhiravan (Green Materials, 2017)
Melanins constitute a class of biomacromolecules that are abundant in nature. Although they exhibit a unique range of physical and chemical properties, their intractable nature has precluded their dissolution in common solvents and facile processing into functional materials. The authors found that commercially available 40 wt% tetrabutylammonium hydroxide (Tbah) solution could yield stable solutions of synthetic and natural melanins at ambient conditions and the dissolution rate could be accelerated by microwave radiation. Transmission electron microscopy images clearly show the disruption of the aggregated structure of melanins in Tbah. Scanning electron microscopy images of melanin/Tbah solutions precipitated in acetone revealed that melanins are dissolved and regenerated and not merely dispersed. To the best of the authors’ knowledge, this is the first report demonstrating a facile approach to solution processing melanins with other biopolymers, which allows leverage of many unique properties of melanins. As an illustrative example, the authors demonstrate here the successful fabrication of cellulose/melanin composite films and fibers and their significant dye absorption capacity (62% reduction) with methylene blue.